2020
DOI: 10.1007/s00198-020-05557-z
|View full text |Cite
|
Sign up to set email alerts
|

The osteoporosis treatment gap in patients at risk of fracture in European primary care: a multi-country cross-sectional observational study

Abstract: This study in 8 countries across Europe found that about 75% of elderly women seen in primary care who were at high risk of osteoporosis-related fractures were not receiving appropriate medication. Lack of osteoporosis diagnosis appeared to be an important contributing factor. Introduction Treatment rates in osteoporosis are documented to be low. We wished to assess the osteoporosis treatment gap in women ≥ 70 years in routine primary care across Europe. Methods This cross-sectional observational study in 8 Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 28 publications
1
78
0
7
Order By: Relevance
“…Although there is no reason for not following these recommendations, at least in high‐income countries with universal healthcare coverage, a wide treatment gap exists between recommended and actual practice. ( 22 ) With this in mind, we have performed a cohort study in the French national healthcare data base. The principal objective was to assess the short‐term consequences of severe osteoporotic fractures at different sites in terms of refracture and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no reason for not following these recommendations, at least in high‐income countries with universal healthcare coverage, a wide treatment gap exists between recommended and actual practice. ( 22 ) With this in mind, we have performed a cohort study in the French national healthcare data base. The principal objective was to assess the short‐term consequences of severe osteoporotic fractures at different sites in terms of refracture and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is treatable and fractures can be prevented [1]. However, it remains largely undiagnosed and untreated [2][3][4]. Fewer than 20% of women and 10% of men experiencing a fragility fracture receive therapies to prevent further fractures [2,3,5].…”
Section: Introductionmentioning
confidence: 99%
“…According to recent reports found that primary care physicians perceive OP as a silent disorder and that is obscure by several health problems as well as it receives less attention manage. [ 23 24 ] The present study will help ensure that primary care physicians take the needed responsibility and for following up bone quality of osteoporotic patients.…”
Section: Discussionmentioning
confidence: 99%